Health education and health promotion among preschool children - Kurowicka, Ewelina (Journal of Education, Health and Sport, 2019)
The most important period for shaping health behavior is human childhood. An important task of parents and kindergarten teachers is to develop healthy eating habits and to encourage sports activities. During the daily educational and didactic classes, teachers implement health education in kindergarten. Cooperation with the local community and organization of meetings with health care representatives are also important. The purpose of this article is to show the essence of health education in kindergarten, with its goals and tasks. The text presents the role of the teacher as a health educator among preschool children.